Doctoral career path studies:exchanging paradigms across international borders - Samuel, Michael Anthony (South African Journal of Higher Education, 2016)
This paper explores four doctoral education studies in the United States of America, the Organisation for Economic Co-operation and Development (OECD), the United Kingdom and France which were presented at the 2012 European Alliance on Research Career Development workshop. These studies were directed towards research funding agencies elaborating new theoretical and methodological insights in this emerging field of doctoral career path studies. What questions do these studies choose to foreground? The studies reveal a general silence about matters of power, hierarchy and marginalisation of doctoral education instead highlighting more pragmatic operational and institutional considerations. The paper generates a set of expanding questions to ask about how the agendas of doctoral career path studies are being constructed and in whose interests they are designed and supported. The paper also offers alternate conceptions of the notion of development, freedoms and significance when evaluating such research agendas, especially for developing world contexts. Key words: doctoral career path studies, career tracking, career outcomes